Scandium bismuth aluminate-lead zirconate titanate piezoelectric ceramic and preparation method thereof

By introducing Al and Zr to replace Sc and Ti in the BS-PT system, a new piezoelectric ceramic component system was constructed, which solved the problem of limited application of existing PZT-based piezoelectric ceramics in high-temperature environments, and achieved efficient piezoelectric performance and high-temperature stability.

CN119638416AActive Publication Date: 2025-03-18NANJING UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411936598.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-18
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing lead zirconium titanate (PZT)-based piezoelectric ceramics are limited in applications in high temperature environments, and the BS-PT system has high raw material costs, high dielectric loss and small mechanical quality factors, which limits its application in high frequency and high temperatures.

Method used

By introducing Al and Zr into the BS-PT system instead of Sc and Ti, the xBiSc1-zAlzO3-(1-x)PbZryTi1-yO3 component system is constructed, and the components and processes are regulated, dielectric loss is reduced and piezoelectric performance is improved.

Benefits of technology

The piezoelectric coefficient d33 is within the range of 171-356pC/N, the Curie temperature is within the range of 346-398°C, the dielectric loss is reduced to 1.30%-1.60%, and the piezoelectric constant change rate is less than 20% from the room temperature to 310°C, which improves high temperature stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638416A_ABST
    Figure CN119638416A_ABST
Patent Text Reader

Abstract

The invention discloses a bismuth scandium aluminate-lead zirconate titanate piezoelectric ceramic and a preparation method thereof, and belongs to the technical field of piezoelectric ceramic materials. The general formula of the piezoelectric ceramic material is xBiSc1-zAlzO3-(1-x) PbZryTi1-yO3, wherein x is more than or equal to 0.2 and less than or equal to 0.7, and y is more than or equal to 0.3 and less than or equal to 0.6; 0.45 < = z < = 0.55. According to the prepared scandium bismuth aluminate-lead zirconate titanate piezoelectric ceramic, the piezoelectric coefficient d33 can reach 356 pC / N, the Curie temperature reaches 346 DEG C, the dielectric loss at the room temperature under the frequency of 1 kHz is 1.60%, meanwhile, the temperature stability of a system is improved, and the change rate of the piezoelectric constant is kept to be smaller than 20% within the range from the room temperature to 310 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of piezoelectric ceramic materials, and in particular to a scandium aluminum bismuth-zirconate titanate piezoelectric ceramic and a preparation method thereof. Background Art

[0002] Piezoelectric ceramics are functional materials that can realize the mutual conversion between mechanical energy and electrical energy. Due to its excellent piezoelectric, dielectric, ferroelectric and other properties, it is currently widely used in sensors, transducers, actuators and energy harvesters. Therefore, the research and preparation of high-performance piezoelectric materials will help promote the upgrading of scientific and technological industrialization and conform to the national strategic key development direction.

[0003] Traditional commercial lead zirconate titanate (PZT)-based piezoelectric ceramics have been widely used in functional devices such as sensors, transducers and actuators. However, due to its low Curie temperature, which is about 380°C at most, PZT-based piezoelectric ceramics are severely limited in their application in high temperature environments. In recent years, a large number of researchers have found that the Curie temperature of the (1-x)BiScO3-xPbTiO3 (BS-PT) ceramic solid solution system at its quasi-modular phase boundary component (x=0.64) can reach 450°C, and the piezoelectric constant d 33 It can reach 460pC / N. In comparison, BS-PT-based piezoelectric ceramics have better high-temperature performance. However, in practical applications, it is found that the raw material Sc2O3 of this system is expensive, and the dielectric loss of this pure phase system is high and the mechanical quality factor is small, which limits its application at high frequency and high temperature. In order to meet people's daily growing production and living needs, further improving the stability of piezoelectric ceramics at high temperatures is of great significance to broaden the width and breadth of applications. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a scandium aluminum bismuth-zirconate titanate piezoelectric ceramic and a preparation method thereof. The scandium aluminum bismuth-zirconate titanate piezoelectric ceramic prepared by the present invention has a piezoelectric coefficient d 33 In the range of 171-356pC / N, the Curie temperature is in the range of 346-398℃, and the dielectric loss at 1kHz frequency at room temperature is reduced to 1.30%-1.60%. At the same time, the temperature stability of the system is improved, and the piezoelectric constant maintains a change rate of less than 20% in the range of room temperature to 310℃.

[0005] The technical solution of the present invention is as follows:

[0006] The first aspect of the present invention protects a bismuth aluminum scandate-lead zirconate titanate piezoelectric ceramic material, the general formula of the piezoelectric ceramic material is: xBiSc 1-z Al z O3-(1-x)PbZr y Ti1-y O3, where 0.2≤x≤0.7, 0.3≤y≤0.6; 0.45≤z≤0.55.

[0007] The second aspect of the present invention protects a method for preparing the bismuth aluminum scandium-lead zirconate titanate piezoelectric ceramic material described in the first aspect, the preparation method comprising the following steps:

[0008] (1) Preparation of base powder

[0009] According to the chemical composition ratio of scandium aluminum bismuth-zirconate titanate piezoelectric ceramic material, Bi2O3, Al2O3, Sc2O3, PbO, ZrO2, and TiO2 are weighed, mixed, ball-milled, dried, sieved, calcined, ball-milled again, and dried to obtain matrix powder;

[0010] (2) Preparation of green body

[0011] Adding polyvinyl alcohol aqueous solution to the base powder of step (1), granulating, and compacting to obtain a green body;

[0012] (3) Preparation of the piezoelectric ceramic material

[0013] The green body obtained in step (2) is placed in a muffle furnace for debinding, cold isostatic pressing and sintering to obtain the scandium aluminum bismuth-zirconate titanate piezoelectric ceramic material.

[0014] Preferably, in step (1), the ball milling conditions are: the material ball water ratio is 1-1.5:2-3:1.5-3, the speed is 300-400 r / min; and the time of each ball milling is 12-24 h.

[0015] Preferably, in step (1), the mesh size of the sieve is 80 to 120 meshes.

[0016] Preferably, in step (1), the drying temperature is 80-100° C. and the drying time is 4-6 hours each time.

[0017] Preferably, in step (1), the heating and cooling rate of the calcination is 4-6°C / min, the calcination temperature is 700-800°C, and the holding time is 4-5h.

[0018] Preferably, in step (2), the mass concentration of the polyvinyl alcohol aqueous solution is 5 to 10 wt %, and the added amount is 3 to 5 mL of the polyvinyl alcohol aqueous solution per 10 g of the base powder.

[0019] Preferably, in step (2), the compaction pressure is 8 to 12 MPa.

[0020] Preferably, in step (3), the binder removal conditions are: a heating and cooling rate of 1 to 2°C / min, a binder removal temperature of 550 to 620°C, and a holding time of 2 to 4h;

[0021] And / or, the conditions of the cold isostatic pressing are: a pressure of 100 to 140 MPa and a holding time of 20 to 40 min.

[0022] Preferably, in step (3), the heating and cooling rate of the sintering is 4 to 6°C / min, the temperature is 1150 to 1250°C, and the holding time is 2 to 4h.

[0023] The beneficial technical effects of the present invention are:

[0024] The present invention introduces a certain amount of Al and Zr into the BS-PT system to replace Sc and Ti at the B position respectively, thereby constructing xBiSc 1-z Al z O3-(1-x)PbZr y Ti 1-y O3 component system, where 0.2≤x≤0.7, 0.3≤y≤0.6, 0.45≤z≤0.55, through component regulation and process optimization, the dielectric loss of the material is reduced, and the piezoelectric performance is relatively excellent (d 33 ≈356pC / N), and the Curie temperature can reach 346℃, which further promoted the development of high-temperature piezoelectric ceramics.

[0025] The preparation of the piezoelectric ceramic of the present invention reduces the cost of the raw materials used, and the preparation process is simple, has good repeatability and is easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The X-ray diffraction pattern of the ceramic material prepared in the embodiment of the present invention.

[0027] In the figure: (a) is the XRD spectrum measured at room temperature, and the test range is 20° to 60°; (b) is a local enlarged view of 43° to 46°.

[0028] Figure 2 The figure is a curve showing the change of dielectric constant of the ceramic material prepared in the embodiment of the present invention with temperature.

[0029] In the figures: (a), Example 1; (b), Example 2; (c), Example 3; (d), Example 4.

[0030] Figure 3 These are the hysteresis loops of the ceramic materials prepared in Examples 1-4 of the present invention.

[0031] Figure 4 is the piezoelectric constant d of the materials of Example 4 and Comparative Example 1 of the present invention33 and their normalized data as a function of annealing temperature.

[0032] In the figure: (a) the change of piezoelectric constant with annealing temperature; (b) the change of piezoelectric constant change rate with annealing temperature. DETAILED DESCRIPTION

[0033] The present invention will be described in detail below in conjunction with the embodiments.

[0034] A scandium aluminum bismuth-zirconate titanate piezoelectric ceramic material, characterized in that the general formula of the piezoelectric ceramic material is: xBiSc 1-z Al z O3-(1-x)PbZr y Ti 1-y O3, where 0.2≤x≤0.7, 0.3≤y≤0.6; 0.45≤z≤0.55. It is referred to as BAS-PZT.

[0035] It can be understood that the present invention introduces a certain amount of Al and Zr into the BS-PT system to replace Sc and Ti at the B position respectively to construct xBiSc 1-z Al z O3-(1-x)PbZr y Ti 1-y O3 component system, where 0.2≤x≤0.7, 0.3≤y≤0.6; 0.45≤z≤0.55, through component regulation and process optimization, the dielectric loss of the material is reduced, and the piezoelectric performance is relatively excellent (d 33 ≈356pC / N), and the Curie temperature is 346℃, which further promoted the development of high-temperature piezoelectric ceramics. Specifically, the present invention introduces more alumina into the Bi-based end member in the BS-PT system, which can reduce the amount of Sc2O3 in the system and greatly reduce the preparation cost; on the other hand, and The difference in ionic radius is large, and dissolving into the lattice will cause a great change in the lattice parameters of the Bi-based end members of the system, aggravating the lattice distortion. The present invention utilizes the lattice distortion caused by substitution to improve the disadvantage of low mechanical quality factor of pure BS-PT piezoelectric ceramic materials, making them less lossy during high temperature and high-frequency vibration, thereby improving the stability and service life of the material.

[0036] In addition, the raw materials used in the present invention contain aluminum oxide, which has the advantages of good thermal stability and low thermal expansion coefficient. When the temperature rises, the atomic vibration is relatively less violent, which can inhibit the phase change process of the ceramic material caused by the temperature increase, thereby achieving piezoelectric performance with excellent temperature stability.

[0037] The present invention will be further described below in conjunction with the embodiments.

[0038] Embodiment 1:

[0039] A bismuth aluminum scandium-lead zirconate titanate piezoelectric ceramic material 0.2BiSc 0.45 Al 0.55 O3-0.8PbZr 0.5 Ti 0.5 O3, the preparation method thereof comprises the following steps:

[0040] (1) Preparation of base powder

[0041] According to 0.2BiSc 0.45 Al 0.55 O3-0.8PbZr 0.5 Ti 0.5 The stoichiometric ratio of O3 is 1:1, Bi2O3, Al2O3, Sc2O3, PbO, ZrO2, and TiO2 are weighed, mixed, ball-milled for 24 hours, dried in an oven at 100°C for 4 hours, and then ground into a uniform powder using a pestle. Then, the powder is sieved using an 80-mesh sieve, placed in a muffle furnace, heated to 800°C at 5°C / min, and calcined for 4 hours. The calcined powder is then ball-milled for a second time for 24 hours, and then dried in an oven at 100°C to obtain a matrix powder. The ball-milling conditions are: the material-ball-water ratio is 1:2:1.5, and the speed is 300r / min.

[0042] (2) Preparation of green body

[0043] To the base powder obtained in step (1), add 4 mL of 7 wt% polyvinyl alcohol aqueous solution per 10 g of powder, place in a mortar, and then use a pestle to fully mix the powder and the binder and grind until the powder is fine, the particle size is uniform, and the fluidity is good. After granulation is completed, it is pressed into a cylindrical blank with a diameter of 10 mm and a thickness of 1 mm under a pressure of 10 MPa.

[0044] (3) Preparation of the piezoelectric ceramic material

[0045] The green body obtained in step (2) is placed in a muffle furnace for debinding, cold isostatic pressing and sintering to obtain the scandium aluminum bismuth-zirconate titanate piezoelectric ceramic material.

[0046] Among them, the process conditions for debinding are: heating and cooling rate of 2℃ / min, debinding temperature of 600℃, and holding time of 3h; the conditions for cold isostatic pressing are: pressure of 120MPa, and holding time of 30min; the process conditions for sintering are: heating and cooling rate of 5℃ / min, sintering temperature of 1200℃, and holding time of 2h.

[0047] In order to reduce the excessive volatilization of Bi and Pb elements in the system, the green body is buried with powder of the same composition before sintering.

[0048] Embodiment 2:

[0049] A bismuth aluminum scandium-lead zirconate titanate piezoelectric ceramic material 0.25BiSc 0.45 Al 0.55 O3-0.75PbZr 0.45 Ti 0.55 O3, the preparation method thereof comprises the following steps:

[0050] (1) Preparation of base powder

[0051] According to 0.25BiSc 0.45 Al 0.55 O3-0.75PbZr 0.45 Ti 0.55 The stoichiometric ratio of O3 is 1:1, Bi2O3, Al2O3, Sc2O3, PbO, ZrO2, and TiO2 are weighed, mixed, ball-milled for 24 hours, dried in an oven at 100°C for 4 hours, and then ground into a uniform powder using a pestle. Then, the powder is sieved using an 80-mesh sieve, placed in a muffle furnace, heated to 800°C at 5°C / min, and calcined for 4 hours. The calcined powder is then ball-milled for a second time for 24 hours, and then dried in an oven at 100°C to obtain a matrix powder. The ball-milling conditions are: the material-ball-water ratio is 1:2:1.5, and the speed is 300r / min.

[0052] (2) Preparation of green body

[0053] To the base powder obtained in step (1), add 4 mL of 7 wt% polyvinyl alcohol aqueous solution per 10 g of powder, place in a mortar, and then use a pestle to fully mix the powder and the binder and grind until the powder is fine, the particle size is uniform, and the fluidity is good. After granulation is completed, it is pressed into a cylindrical blank with a diameter of 10 mm and a thickness of 1 mm under a pressure of 10 MPa.

[0054] (3) Preparation of the piezoelectric ceramic material

[0055] The green body obtained in step (2) is placed in a muffle furnace for debinding, cold isostatic pressing and sintering to obtain the scandium aluminum bismuth-zirconate titanate piezoelectric ceramic material.

[0056] Among them, the process conditions for debinding are: heating and cooling rate of 2℃ / min, debinding temperature of 600℃, and holding time of 3h; the conditions for cold isostatic pressing are: pressure of 120MPa, and holding time of 30min; the process conditions for sintering are: heating and cooling rate of 5℃ / min, sintering temperature of 1200℃, and holding time of 2h.

[0057] In order to reduce the excessive volatilization of Bi and Pb elements in the system, the green body is buried with powder of the same composition before sintering.

[0058] Embodiment 3:

[0059] A bismuth aluminum scandium-lead zirconate titanate piezoelectric ceramic material 0.3BiSc 0.45 Al 0.55 O3-0.7PbZr 0.45 Ti 0.55 A method for preparing O3, the method comprising the following steps:

[0060] (1) Preparation of base powder

[0061] According to 0.3BiSc 0.45 Al 0.55 O3-0.7PbZr 0.45 Ti 0.55 The stoichiometric ratio of O3 is 1:1, Bi2O3, Al2O3, Sc2O3, PbO, ZrO2, and TiO2 are weighed, mixed, ball-milled for 24 hours, dried in an oven at 100°C for 4 hours, and then ground into a uniform powder using a pestle. Then, the powder is sieved using an 80-mesh sieve, placed in a muffle furnace, heated to 800°C at 5°C / min, and calcined for 4 hours. The calcined powder is then ball-milled for a second time for 24 hours, and then dried in an oven at 100°C to obtain a matrix powder. The ball-milling conditions are: the material-ball-water ratio is 1:2:1.5, and the speed is 300r / min.

[0062] (2) Preparation of green body

[0063] To the base powder obtained in step (1), add 4 mL of 7 wt% polyvinyl alcohol aqueous solution per 10 g of powder, place in a mortar, and then use a pestle to fully mix the powder and the binder and grind until the powder is fine, the particle size is uniform, and the fluidity is good. After granulation is completed, it is pressed into a cylindrical blank with a diameter of 10 mm and a thickness of 1 mm under a pressure of 10 MPa.

[0064] (3) Preparation of the piezoelectric ceramic material

[0065] The green body obtained in step (2) is placed in a muffle furnace for debinding, cold isostatic pressing and sintering to obtain the scandium aluminum bismuth-zirconate titanate piezoelectric ceramic material.

[0066] Among them, the process conditions for debinding are: heating and cooling rate of 2℃ / min, debinding temperature of 600℃, and holding time of 3h; the conditions for cold isostatic pressing are: pressure of 120MPa, and holding time of 30min; the process conditions for sintering are: heating and cooling rate of 5℃ / min, sintering temperature of 1200℃, and holding time of 2h.

[0067] In order to reduce the excessive volatilization of Bi and Pb elements in the system, the green body is buried with powder of the same composition before sintering.

[0068] Embodiment 4:

[0069] A bismuth aluminum scandium-lead zirconate titanate piezoelectric ceramic material 0.25BiSc 0.45 Al 0.55 O3-0.75PbZr 0.35 Ti 0.65 A method for preparing O3, the method comprising the following steps:

[0070] (1) Preparation of base powder

[0071] According to 0.25BiSc 0.45 Al 0.55 O3-0.75PbZr 0.35 Ti 0.65 The stoichiometric ratio of O3 is 1:1, Bi2O3, Al2O3, Sc2O3, PbO, ZrO2, and TiO2 are weighed, mixed, ball-milled for 24 hours, dried in an oven at 100°C for 4 hours, and then ground into a uniform powder using a pestle. Then, the powder is sieved using an 80-mesh sieve, placed in a muffle furnace, heated to 800°C at 5°C / min, and calcined for 4 hours. The calcined powder is then ball-milled for a second time for 24 hours, and then dried in an oven at 100°C to obtain a matrix powder. The ball-milling conditions are: the material-ball-water ratio is 1:2:1.5, and the speed is 300r / min.

[0072] (2) Preparation of green body

[0073] To the base powder obtained in step (1), add 4 mL of 7 wt% polyvinyl alcohol aqueous solution per 10 g of powder, place in a mortar, and then use a pestle to fully mix the powder and the binder and grind until the powder is fine, the particle size is uniform, and the fluidity is good. After granulation is completed, it is pressed into a cylindrical blank with a diameter of 10 mm and a thickness of 1 mm under a pressure of 10 MPa.

[0074] (3) Preparation of the piezoelectric ceramic material

[0075] The green body obtained in step (2) is placed in a muffle furnace for debinding, cold isostatic pressing and sintering to obtain the scandium aluminum bismuth-zirconate titanate piezoelectric ceramic material.

[0076] Among them, the process conditions for debinding are: heating and cooling rate of 2℃ / min, debinding temperature of 600℃, and holding time of 3h; the conditions for cold isostatic pressing are: pressure of 120MPa, and holding time of 30min; the process conditions for sintering are: heating and cooling rate of 5℃ / min, sintering temperature of 1200℃, and holding time of 2h.

[0077] In order to reduce the excessive volatilization of Bi and Pb elements in the system, the green body is buried with powder of the same composition before sintering.

[0078] Example 5

[0079] A bismuth aluminum scandium-lead zirconate titanate piezoelectric ceramic material 0.2BiSc 0.45 Al 0.55 O3-0.8PbZr 0.5 Ti 0.5 O3, the preparation method thereof comprises the following steps:

[0080] (1) Preparation of base powder

[0081] According to 0.2BiSc 0.45 Al 0.55 O3-0.8PbZr 0.5 Ti 0.5 The stoichiometric ratio of O3 is 1:1, Bi2O3, Al2O3, Sc2O3, PbO, ZrO2, and TiO2 are weighed, mixed, ball-milled for 12 hours, dried in an oven at 80°C for 6 hours, and then ground into a uniform powder using a pestle. Then, the powder is sieved using a 100-mesh sieve, placed in a muffle furnace, heated to 700°C at 4°C / min, and calcined for 4.5 hours. The calcined powder is then ball-milled for a second time for 12 hours, and then dried in an oven at 80°C to obtain a matrix powder. The ball-milling conditions are: the material-ball-water ratio is 1.2:2.5:2.0, and the speed is 350r / min.

[0082] (2) Preparation of green body

[0083] To the base powder obtained in step (1), add 3 mL of 5 wt% polyvinyl alcohol aqueous solution per 10 g of powder, place in a mortar, and then use a pestle to fully mix the powder and the binder and grind until the powder is fine, the particle size is uniform, and the fluidity is good. After granulation is completed, it is pressed into a cylindrical blank with a diameter of 10 mm and a thickness of 1 mm under a pressure of 8 MPa.

[0084] (3) Preparation of the piezoelectric ceramic material

[0085] The green body obtained in step (2) is placed in a muffle furnace for debinding, cold isostatic pressing and sintering to obtain the scandium aluminum bismuth-zirconate titanate piezoelectric ceramic material.

[0086] Among them, the process conditions for debinding are: heating and cooling rate of 1℃ / min, debinding temperature of 550℃, and holding time of 2h; the conditions for cold isostatic pressing are: pressure of 100MPa, and holding time of 20min; the process conditions for sintering are: heating and cooling rate of 4℃ / min, sintering temperature of 1150℃, and holding time of 3h.

[0087] In order to reduce the excessive volatilization of Bi and Pb elements in the system, the green body is buried with powder of the same composition before sintering.

[0088] Example 6

[0089] A bismuth aluminum scandium-lead zirconate titanate piezoelectric ceramic material 0.2BiSc 0.45 Al 0.55 O3-0.8PbZr 0.5 Ti 0.5 O3, the preparation method thereof comprises the following steps:

[0090] (1) Preparation of base powder

[0091] According to 0.2BiSc 0.45 Al 0.55 O3-0.8PbZr 0.5 Ti 0.5 The stoichiometric ratio of O3 is 1:1, Bi2O3, Al2O3, Sc2O3, PbO, ZrO2, and TiO2 are weighed, mixed, and ball-milled for 20 hours. After drying in a 90°C oven for 5 hours, the powder is ground with a pestle, and then sieved with a 120-mesh sieve, placed in a muffle furnace, heated to 750°C at 6°C / min and calcined for 5 hours. The calcined powder is then ball-milled for a second time for 20 hours, and then dried in a 90°C oven to obtain the matrix powder. The ball-milling conditions are: the material-ball-water ratio is 1.5:3:3, and the speed is 400r / min.

[0092] (2) Preparation of green body

[0093] To the base powder obtained in step (1), add 5 mL of 10 wt% polyvinyl alcohol aqueous solution per 10 g of powder, place in a mortar, and then use a pestle to fully mix the powder and the binder and grind until the powder is fine, the particle size is uniform, and the fluidity is good. After granulation is completed, it is pressed into a cylindrical blank with a diameter of 10 mm and a thickness of 1 mm under a pressure of 12 MPa.

[0094] (3) Preparation of the piezoelectric ceramic material

[0095] The green body obtained in step (2) is placed in a muffle furnace for debinding, cold isostatic pressing and sintering to obtain the scandium aluminum bismuth-zirconate titanate piezoelectric ceramic material.

[0096] Among them, the process conditions for debinding are: heating and cooling rate of 1.5℃ / min, debinding temperature of 620℃, and holding time of 4h; the conditions for cold isostatic pressing are: pressure of 140MPa, and holding time of 40min; the process conditions for sintering are: heating and cooling rate of 6℃ / min, sintering temperature of 1250℃, and holding time of 4h.

[0097] In order to reduce the excessive volatilization of Bi and Pb elements in the system, the green body is buried with powder of the same composition before sintering.

[0098] Comparative Example 1:

[0099] A bismuth scandate-lead titanate-based piezoelectric ceramic material 0.36BS-0.64PT, the preparation method of which comprises the following steps:

[0100] (1) Preparation of base powder

[0101] According to the stoichiometric ratio of 0.36BS-0.64PT, Bi2O3, Sc2O3, PbO, and TiO2 were weighed, mixed, ball-milled for 24 hours, dried in an oven at 100°C for 4 hours, and then ground with a pestle to make the powder uniform. Then, the powder was sieved with an 80-mesh sieve, placed in a muffle furnace, heated to 800°C at 5°C / min, and calcined for 4 hours. The calcined powder was then ball-milled for a second time for 24 hours, and then dried in an oven at 100°C to obtain the desired matrix powder. The ball-milling conditions are: the material-ball-water ratio is 1:2:1.5, and the speed is 300r / min.

[0102] (2) Preparation of green body

[0103] To the powder obtained in step (1), add 4 mL of 7 wt% polyvinyl alcohol aqueous solution per 10 g of powder, place in a mortar, and then use a pestle to fully mix the powder and the binder and grind until the powder is fine, the particle size is uniform, and the fluidity is good. After granulation is completed, it is pressed into a cylindrical blank with a diameter of 10 mm and a thickness of 1 mm under a pressure of 10 MPa.

[0104] (3) Preparation of the piezoelectric ceramic material

[0105] The green body obtained in step (2) is placed in a muffle furnace for debinding, cold isostatic pressing and sintering to obtain the bismuth scandate-lead titanate-based piezoelectric ceramic material.

[0106] Among them, the process conditions for debinding are: heating and cooling rate of 2℃ / min, debinding temperature of 600℃, and holding time of 3h; the conditions for cold isostatic pressing are: pressure of 120MPa, and holding time of 30min; the process conditions for sintering are: heating and cooling rate of 5℃ / min, sintering temperature of 1000℃, and holding time of 2h.

[0107] In order to reduce the excessive volatilization of Bi and Pb elements in the system, the green body is buried with powder of the same composition before sintering.

[0108] Test example:

[0109] The piezoelectric ceramic materials prepared in the above embodiments and comparative examples were polished, electroded and polarized, the polarization electric field was 40-50 kV / cm, the polarization time was 20 min, and the polarization temperature was 120°C; a 4294A impedance analyzer was used to measure the dielectric loss of the polarized samples at a frequency of 1 kHz at room temperature, a quasi-static d33 instrument was used to measure the piezoelectric properties of the polarized samples, and a Linkam variable temperature system was used in conjunction with HP 4284A to measure the dielectric temperature spectrum of the material. The comprehensive performance is shown in Table 1 below.

[0110] Table 1 Performance tests of embodiments and comparative examples

[0111]

[0112] As can be seen from the above table, the piezoelectric coefficient of the scandium aluminum bismuth-zirconate titanate piezoelectric ceramic of the embodiment can reach 356pC / N, the Curie temperature can reach 346°C, and the dielectric loss at a frequency of 1kHz at room temperature is 1.60%. Although the piezoelectric coefficient and Curie temperature of the comparative example are improved, its dielectric loss is more than 1 times greater than that of the embodiment, and the mechanical quality factor Qm is much smaller than that of the embodiment, which greatly limits its high-temperature stability, thereby making the depolarization behavior of the comparative example more likely to occur than that of the embodiment. The ceramic material of the embodiment of the present invention reduces the dielectric loss and improves the high-temperature stability while obtaining the largest possible piezoelectric coefficient and Curie temperature.

[0113] Figure 1 The X-ray diffraction pattern of the ceramic material prepared in the embodiment of the present invention. Figure 1 (a) is the XRD spectrum of the ceramic materials of each embodiment and comparative example measured at room temperature, 0.2BAS-0.8PZ 0.5 T 0.5 Corresponding to Example 1: 0.25BAS-0.75PZ 0.45 T 0.55 Corresponding to Example 2: 0.3BAS-0.7PZ 0.45 T 0.55 Corresponding to Example 3: 0.25BAS-0.75PZ 0.35 T 0.65 Corresponding to Example 4; the test range is 20° to 60°, Figure 1 (b) is a partial enlarged view of 44° to 46°. According to Example 4 in Figure b, i.e. 0.25BAS-0.75PZ 0.35 T 0.65 For the component ceramics, the splitting of the (200) peak shows that the crystal phase structure is mainly composed of rhombohedral and tetragonal phases, and the system phase structure is at the quasi-monotonic phase boundary, so the piezoelectric performance of the system is optimal.

[0114] Figure 2The dielectric constant and dielectric loss curves of the ceramic materials prepared in Examples 1-4 of the present invention at frequencies of 1kHz, 10kHz, 100kHz and 500kHz are respectively plotted as a function of temperature. It can be seen from the figure that the Curie temperatures of piezoelectric ceramics of different components differ greatly, but the corresponding dielectric losses are relatively small, which is conducive to their application under high temperature conditions.

[0115] Figure 3 The hysteresis loops of the ceramic materials prepared in the embodiments of the present invention show that, by comparison, the residual polarization intensity of the sample in Embodiment 4 is the largest, and the piezoelectric performance of the corresponding system is the best.

[0116] The present invention performs annealing on ceramic materials of different components to test the high temperature stability of piezoelectric ceramic materials. After polarization, the piezoelectric ceramics of the embodiment and the comparative example are placed in a muffle furnace at different temperatures for annealing for 1 hour, and then cooled to room temperature to measure the d 33 The specific results are as follows Figure 4 As shown in the figure, the piezoelectric constant of the sample in Comparative Example 1 decreases rapidly with the increase of annealing temperature, and its piezoelectric performance change rate in the temperature range from room temperature to 275°C is less than 20%, while the 0.25BAS-0.75PZ 0.35 T 0.65 The temperature stability of the system has been greatly improved, and its piezoelectric performance changes by less than 20% in the temperature range from room temperature to 310°C, which has better prospects for high-temperature applications.

[0117] The present invention introduces a certain amount of Al and Zr into the BS-PT system to replace Sc and Ti at the B position respectively. On the one hand, the amount of Sc2O3 in the system can be reduced, greatly reducing the preparation cost. On the other hand, the lattice distortion caused by ion substitution is utilized to improve the dielectric loss of the material, thereby improving the stability and service life of the material.

[0118] The above is only a preferred embodiment of the present invention, and the present invention is not limited to the above embodiments. It is understood that other improvements and changes directly derived or associated by those skilled in the art without departing from the spirit and concept of the present invention should be considered to be included in the protection scope of the present invention.

Claims

1. A scandium aluminum bismuth-zirconate titanate piezoelectric ceramic material, characterized in that: The general formula of the piezoelectric ceramic material is: xBiSc 1-z Al z O3-(1-x)PbZr y Ti 1-y O3, where 0.2≤x≤0.7, 0.3≤y≤0.6; 0.45≤z≤0.

55.

2. A method for preparing the scandium aluminum bismuth-zirconate titanate piezoelectric ceramic material according to claim 1, characterized in that: The preparation method comprises the following steps: (1) Preparation of base powder According to the chemical composition ratio of scandium aluminum bismuth-zirconate titanate piezoelectric ceramic material, Bi2O3, Al2O3, Sc2O3, PbO, ZrO2, and TiO2 are weighed, mixed, ball-milled, dried, sieved, calcined, ball-milled again, and dried to obtain matrix powder; (2) Preparation of green body Adding polyvinyl alcohol aqueous solution to the base powder of step (1), granulating, and compacting to obtain a green body; (3) Preparation of the piezoelectric ceramic material The green body obtained in step (2) is placed in a muffle furnace for debinding, cold isostatic pressing and sintering to obtain the scandium aluminum bismuth-zirconate titanate piezoelectric ceramic material.

3. The preparation method according to claim 2, characterized in that: In step (1), the ball milling conditions are: the material-ball-water ratio is 1-1.5:2-3:1.5-3, the speed is 300-400 r / min; and the time of each ball milling is 12-24 h.

4. The preparation method according to claim 2, characterized in that: In step (1), the mesh size of the sieve is 80 to 120 meshes.

5. The preparation method according to claim 2, characterized in that: In step (1), the drying temperature is 80-100° C. and the drying time is 4-6 hours each time.

6. The preparation method according to claim 2, characterized in that: In step (1), the heating and cooling rate of the calcination is 4-6°C / min, the calcination temperature is 700-800°C, and the holding time is 4-5h.

7. The preparation method according to claim 2, characterized in that: In step (2), the mass concentration of the polyvinyl alcohol aqueous solution is 5-10wt%, and the added amount is 3-5mL of polyvinyl alcohol aqueous solution per 10g of base powder.

8. The preparation method according to claim 2, characterized in that: In step (2), the compaction pressure is 8 to 12 MPa.

9. The preparation method according to claim 2, characterized in that: In step (3), the debinding conditions are: heating and cooling rate is 1-2°C / min, debinding temperature is 550-620°C, and holding time is 2-4h; And / or, the conditions of cold isostatic pressing are: pressure of 100-140 MPa, and holding time of 20-40 min.

10. The preparation method according to claim 2, characterized in that: In step (3), the heating and cooling rate of the sintering is 4 to 6°C / min, the temperature is 1150 to 1250°C, and the holding time is 2 to 4h.

Citation Information

Patent Citations

  • Bismuth zirconate manganate-bismuth scandate-lead titanate piezoelectric ceramic material and preparation method thereof

    CN111269009A

  • Piezoelectric energy collection ceramic material with high depolarization temperature and large piezoelectric property and preparation

    CN118619663A

  • Piezoelectric / electrostrictive ceramic composition

    JP2009221096A

  • PIEZOCERAMIC MATERIAL

    RU2010139031A